Evaluation of antioxidant and neuroprotective activities of Cassia fistula (L.) using the Caenorhabditis elegans model - Thabit, Sara; Roxo, Mariana; Wink, Michael (PeerJ, 2018)
Background Cassia fistula (L.) (Fabaceae) is a medicinal plant from tropical Asia. It is known for its marked antioxidant activity, which is attributed to its high phenolic content. The present study aims at testing both the antioxidant and neuroprotective effects of a hydroalcoholic extract from the aerial parts of Cassia fistula using the Caenorhabditis elegans model, which is widely used in this context. Methods Chemical profiling of secondary metabolites that seem to be responsible for both antioxidant and neuroprotective capacities was carried out by HPLC/PDA/ESI-MSn. Antioxidant activity was tested in vitro by CUPRAC and DPPH assays. In vivo antioxidant and neuroprotective activities were investigated using the C. elegans model. Results The Cassia extract improved the survival rate of the nematodes and protected them against oxidative stress. In addition, a decrease in the accumulation of reactive oxygen species (ROS) was observed. The important role of DAF-16/FOXO pathway was confirmed through an increased nuclear localization of the DAF-16 transcription factor, increased expression of SOD-3 stress response gene and decreased expression of HSP-16.2. Furthermore, the putative involvement of SKN-1/NRF2 pathway was demonstrated by a decrease in GST-4 levels. A neuroprotective activity of the Cassia extract was shown by a decline in polyglutamine (polyQ40) aggregate formation and a delay in paralysis caused by amyloid beta (Aβ1-42) accumulation. Discussion The Cassia extract exhibits substantial antioxidant and neuroprotective activities in vivo, which might provide a rich and novel source of natural antioxidants and neuroprotective compounds to be further studied for the use in various food and cosmetic industrial fields.
Gesehen am 31.07.2019